The Public Papers of Governor Brereton C. Jones, 1991-1995 - Jones, Brereton (Book collections on Project MUSE., 2001)
In his inaugural address, Governor Brereton C. Jones proclaimed, ""This administration is committed to having the most positive, progressive, exciting four years in our state's history.""Through speeches and press releases, this volume reflects the principal concerns of Jones's time in office. Thematically organized, the more than two hundred public statements included here present the public face of the Jones administration on such issues as health care, education, economic development, the environment, and governmental reform. Nowhere else has the full text of these speeches and press releas.